Health Literacy and Affecting Factors in Individuals with Stroke: A Cross-Sectional Study. - KALAV, Simge; BULUT, Ebru; TARLABELEN KARAYTUĞ, Emine; ÇEVİK AKYIL, Rahşan (Journal of Nursology, 2025)
Objective: This study aimed to examine the factors affecting the health literacy of individuals with stroke. Methods: In this analytical and cross-sectional study, "Sociodemographic Characteristics Form" and "the Health Literacy Scale" were administered to 223 individuals with stroke who were hospitalized in the neurology clinic of a university hospital in western Turkey. The research data were analyzed in the "Statistical Package for the Social Sciences 22" program. Kolmogorov-Smirnov test, Pearson Correlation, Mann Whitney U", "Kruskal Wallis", and "Post Hoc/Games-Howell" tests were used. Results: The total mean scale score in our study was 88.67±22.36. The mean rank values of the individuals, who were aged below 50, who had a high education level, and who did not have a chronic disease other than stroke, on the scale and all its subscales were significantly higher. The mean rank of the scale increased as the economic status raised from low to high. The mean rank value of those who received training from health professionals on the "access to information subscale" was significantly higher. Conclusion: Age, marital status, education level, income level, general health status, presence of another chronic disease, and status of receiving training from a health professional were determined as factors affecting health literacy in individuals with stroke. It is thought that determining the health literacy levels of inpatients with stroke is an important step in determining the stroke literacy levels of individuals and thus their awareness of stroke.